Hypoxic Tumor Kinase Signaling Mediated by STAT5A in Development of Castration-Resistant Prostate Cancer. - Marignol, Laure (My University, 2013)
In this study, we hypothesized that androgen-deprivation therapy (ADT) in prostate cancer, although initially efficient, induces changes in the tumor kinome, which subsequently promote development of castration-resistant (CR) disease. Recognizing the correlation between tumor hypoxia and poor prognosis in prostate cancer, we further hypothesized that such changes might be influenced by hypoxia. Microarrays with 144 kinase peptide substrates were applied to analyze CWR22 prostate carcinoma xenograft samples from ADT-naïve, androgen-deprived (AD), long-term AD (ADL), and CR disease stages. The impact of hypoxia was assessed by matching the xenograft kinase activity profiles with those acquired from hypoxic and normoxic prostate carcinoma cell cultures, whereas the clinical relevance was evaluated by analyzing prostatectomy tumor samples from patients with locally advanced disease, either in ADT-naïve or early CR disease stages. By using this novel peptide substrate microarray method we revealed high kinase activity mediated by signal transducer and activator of transcription 5A (STAT5A) in CR prostate cancer. Additionally, we uncovered high STAT5A kinase activity already in regressing ADL xenografts, before renewed CR growth was evidenced. Finally, since increased STAT5A kinase activity also was detected after exposing prostate carcinoma cells to hypoxia, we propose long-term ADT to induce tumor hypoxia and stimulate STAT5A kinase activity, subsequently leading to renewed CR tumor growth. Hence, the study detected STAT5A as a candidate to be further investigated for its potential as marker of advanced prostate cancer and as possible therapeutic target protein.
PUBLISHED
Keywords: Carcinomas